Tumor-Associated Macrophages as Key Modulators of Disease Progression in Diffuse Large B-Cell Lymphoma - Corina Joldes; Laura Jimbu; Oana Mesaros; Mihnea Zdrenghea; Bogdan Fetica (Biomedicines)
With the advent of new therapeutic approaches, there is hope that anticancer treatment will eventually be possible without the use of chemotherapy. Efficient immunotherapeutic options have recently emerged in many cancers, offering a less aggressive approach, with overall better tolerance, making them also suitable for frail patients. Response to immunotherapy relies on the availability, functionality, and efficacy of the host’s immune effector mechanisms. One of the key factors determining the efficacy of immunotherapy is the tumor microenvironment, which encompasses various immune effectors, including macrophages, which play a crucial role in regulating immune responses through phagocytosis and antigen presentation. Macrophages are prototypically divided, according to their polarization, into either the pro-inflammatory M1 type or the anti-inflammatory M2 type. In the tumor microenvironment, M2-polarized macrophages, known as tumor-associated macrophages (TAMs), are the predominant phenotype and are associated with tumor progression. The M1/M2 paradigm contributes to the understanding of tumor progression. Due to the variable microenvironment, the mechanisms regulating TAMs can vary across different cancers. Variations in TAM polarization may account for the different treatment responses in patients with similar diseases. This paper investigates the connection between TAMs, disease progression, and treatment responses in the most frequent solid hematologic cancer, diffuse large B-cell lymphoma.